Clinical safety of an MRI conditional implantable cardioverter defibrillator system: A prospective Monocenter ICD‐Magnetic resonance Imaging feasibility study (MIMI). Issue 3 (3rd September 2015) - Kypta, Alexander; Blessberger, Hermann; Hoenig, Simon; Saleh, Karim; Lambert, Thomas; Kammler, Juergen; Fellner, Franz; Lichtenauer, Michael; Steinwender, Clemens
Abstract : Background: The aim of this study was to evaluate the safety and efficacy of the Lumax 740 ® Implantable Cardioverter Defibrillator (ICD) system in patients undergoing a defined 1.5 Tesla (T) MRI. Materials and Methods: Between November 2013 and April 2014, eighteen patients (age range, 41–78 years; mean age, 64 years) implanted with a Lumax 740 ® ICD system for at least 6 weeks before an MRI were enrolled into this single‐center feasibility study. The local ethics committee approved the study before patients gave written informed consent. Patients underwent defined MRI 1.5T of the brain and lower lumbar spine with three safety follow‐up evaluations obtained during the 3‐month study period. Data were analyzed descriptively. Study endpoints were the absence of either MRI and pacing system related serious adverse device effects (SADE), or of a ventricular pacing threshold increase >0.5V, or of an R‐wave amplitude attenuation < 50%, or of an R‐wave amplitude < 5.0 mV at 1‐month follow‐up. The assessment of safety and efficacy was supported by recording of all adverse events, changes in pacing threshold, R‐wave sensing, pacing impedances and in battery status. Results: Sixteen patients completed the MRI and the follow‐up period. As no SADE occurred, the SADE free rate was 100%. Freedom from ventricular pacing threshold increase was 100% (16/16; 95%CI: 82.9%; 100.0%). There were no significant differences between baseline and follow‐up measurements of sensing amplitudes (−0.58 ± 2.07 mV, P  = 0.239, −0.41 ± 1.04 mV, P  = 0.133, and −0.25 ± 1.36 mV, P  = 0.724, for immediately after, 1 month and 3 months after MRI scan, respectively) and pacing thresholds (−0.047 ± 0.18 V, P  = 0.317, −0.019 ± 0.11 V, P  = 0.490, and 0.075 ± 0.19 V, P  = 0.070, for immediately after, 1 month and 3 months after MRI scan, respectively). Lead impedances after the MRI scan were significantly lower as compared with baseline values (−22.8 ± 21.69 Ω, P  = 0.001, −21.62 ± 39.71 Ω, P  = 0.040, and −33.68 ± 57.73 Ω, P  = 0.018, for immediately after, 1 month and 3 months after MRI scan, respectively). Conclusion: MRI scans in patients with MRI conditional ICD system (Lumax 740 ® ) are feasible and can be performed safely under defined conditions in a hospital setting.J. Magn. Reson. Imaging 2015. J. MAGN. RESON. IMAGING 2016;43:574–584.